MSH2-Dependent Germinal CTG Repeat Expansions Are Produced Continuously in Spermatogonia from DM1 Transgenic Mice - Savouret, Cédric (American Society for Microbiology, 2004)
Myotonic dystrophy type 1 is a neuromuscular affection associated with the expansion of an unstable CTG repeat in the DM protein kinase gene. The disease is characterized by somatic tissue-specific mosaicism and very high intergenerational instability with a strong bias towards expansions. We used transgenic mice carrying more than 300 unstable CTG repeats within their large human genomic environment to investigate the dynamics of CTG repeat germinal mosaicism in males. Germinal mosaicism towards expansions was already present in spermatozoa at 7 weeks of age and continued to increase with age, suggesting that expansions are continuously produced throughout life. To determine the precise stage at which germinal expansions occur during spermatogenesis, we sorted and collected the different germ cell types produced during spermatogenesis from males of different ages and analyzed the CTG repeat mosaicism in each fraction. Strong mosaicisms towards expansions were already observed in spermatogonia before meiosis. In transgenic Msh2-deficient mice, germinal instability of the CTG repeats (only contractions) also occurs premeiotically. No significant difference in mosaicism was detected between spermatogonia and spermatozoa, arguing against continued expansions during postmeiotic stages. This indicates that germinal expansions are produced at the beginning of spermatogenesis, in spermatogonia, by a meiosis-independent mechanism involving MSH2.